Hopf bifurcation in a model of sustainable development - Granada Díaz, Héctor Andrés; A.G, Miguel Angel; Moreno A, D.K; Canchila M, J.A (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article presents a system of three first-orden ordinary differential equations to study the dynamic in- teraction between renewable resources, population and environmental pollution in a region. The model is achieved coupling a dynamic equation of contamination to formulated systems by Simone D’alessandro and shows that under the Hopf bifurcation can be found conditions to achieve sustainable development under the definition given in the report of Brundtland commission 1987. That is, when a harmonic balance between the state variables of the model is reached.